Analisa Perbandingan Kinerja Pelayanan Transportasi Online Roda Empat terhadap Masyarakat Kota Padang - Gunawan, Hendra; Martanto Adji, Bayu; Setia Budi Idaman, Muhammad (Universitas Andalas, 2023)
The use of transportation services as a community needs continues to increase. To make it easier for people to carry out their daily activities, online transportation services are available, both two-wheeled and four-wheeled. In Padang City, four-wheeled online transportation is served by three service providers, namely GoCar, GrabCar, and MaximCar. The presence of four-wheeled online transportation is very helpful in serving people's daily transportation needs. The aim of this research is to determine the performance of four-wheeled online transportation services and compare the performance of each in serving the people of Padang City. The method used is the Importance Performance Analysis (IPA) method. Data was collected using a questionnaire with 150 respondents, who were users of four-wheeled online transportation services in Padang City. The analysis results show that the highest satisfaction felt by the people of Padang City is with the services provided by GoCar.